An uncommon association of H-type tracheoesophageal fistula with infantile hypertrophic pyloric stenosis - Oğuzkurt, Pelin; Tanyel, F. Cahit; Haliloğlu, Mithat; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 1999)
Although infantile hypertrophic pyloric stenosis following esophageal atresia repair is known, infantile hypertrophic pyloric stenosis following H-type tracheoesophageal fistula has not been encountered previously. A case of H-type tracheoesophageal fistula and infantile hypertrophic pyloric stenosis is presented. The patient, operated on for H-type fistula, a rare congenital anomaly of the esophagus, on the tenth day of life was readmitted 19 days later because of continous vomiting after every feeding. The clinical findings and physical and radiological examinations revealed infantile hypertrophic pyloric stenosis which required surgical treatment. It is suggested that the association of H-type tracheoesophageal fistula with infantile hypertrophic pyloric stenosis is coincidental, given the estimated incidence of one in every 84,375,000 males and 337,500,000 females.
Keywords: hypertrophic pyloric stenosis; H-type tracheoesophageal fistula